Modeling Small Scale Weather with Cellular Automata - Litzau, Kathryn; Wisby, Matthew (My University, 2013)
A standard two-dimensional cellular automaton is a discrete model that changes over time steps by sets of rules that govern the cells. The purpose of this study was to use cellular automata to model small scale weather patterns.
Color poster with text, diagrams, and images.
Keywords: Weather simulation; Cellular automaton; Posters